Corak Akhbari dalam Tafsir Syi'ah - Fikriyati, Ulya (Lajnah Pentashihan Mushaf Al-Qur'an, 2012)
This paper is going to confirm that the pattern of the traditionist (akhbari) is not just a trend in the Shi'i thought in the 11th century, but has played a significant role as a trigger of Shiite intellectual stretching (movement). Along the way, the style of Traditionist is divided into two styles namely the Pure Traditionists style and Neo-Traditionists style. The study would alsoÂ like to correct the conclusion that Al-Burhan fi Tafsir al-Qur'an is the Qur'anic exegesis that really represents the pattern of the pure traditionist thought, because not all of the narrations in the book came from the Prophet or the family of the prophet (ahli al-bait), besides, Bahrani himself does not strictly apply the basic principles of the traditionists school.